Chasing the sun: Qu Leilei's serial images in early post-Mao China. (1st September 2019) - Lee, Jennifer Dorothy
Abstract'You always treat the sun as though it were yours.' Lining the frame of a pen-and-ink sketch, these words reflect conditions of possibility particular to the contemporaneity of early post-Mao China. Included in his Visual Diary series from the early 1980s, Qu Leilei's image-text turns inward the heavily socialized forms of visual and political expression from the revolutionary era. As instances of the artist's emerging private practice, such works, including etchings, line drawings, and fragments of prose poetry, are seldom addressed in existing scholarship on contemporary Chinese art. This article takes up a selective examination of Qu's diaristic ephemera from this historical moment following the Cultural Revolution (1966‐76) to explore how Qu's entries both maintain and transform aspects of revolutionary-era media and visuality. The article further considers the following questions: In what ways does Qu's Visual Diary reconfigure the serial images of revolutionary state-driven practices in the social landscape of still-Maoist Beijing? How do Qu's transfigured image-texts complicate the rejection of Maoist visual vanguardism in cultural practices after the revolution?